Wnt/β-Catenin and noncanonical Wnt signaling interact in tissue evagination in the simple eumetazoan Hydra - Philippe, Isabelle; Özbek, Suat; Watanabe, Hiroshi; Holstein, Thomas W. (Proceedings of the National Academy of Sciences of the United States of America, 2009)
In and evaginations of 2D cell sheets are major shape generating processes in animal development. They result from directed movement and intercalation of polarized cells associated with cell shape changes. Work on several bilaterian model organisms has emphasized the role of noncanonical Wnt signaling in cell polarization and movement. However, the molecular processes responsible for generating tissue and body shape in ancestral, prebilaterian animals are unknown. We show that noncanonical Wnt signaling acts in mass tissue movements during bud and tentacle evagination and regeneration in the cnidarian polyp Hydra. The wnt5, wnt8, frizzled2 (fz2), and dishevelled-expressing cell clusters define the positions, where bud and tentacle evaginations are initiated; wnt8, fz2, and dishevelled remain up-regulated in those epithelial cells, undergoing cell shape changes during the entire evagination process. Downstream of wnt and dsh expression, JNK activity is required for the evagination process. Multiple ectopic wnt5, wnt8, fz2, and dishevelled-expressing centers and the subsequent evagination of ectopic tentacles are induced throughout the body column by activation of Wnt/β-Catenin signaling. Our results indicate that integration of axial patterning and tissue morphogenesis by the coordinated action of canonical and noncanonical Wnt pathways was crucial for the evolution of eumetazoan body plans.
Gesehen am 26.06.2017